The relevance of certain design elements on the association between accounting and market-based measures of risk on the JSE - E. D. Loxton; W. D. Hamman; E. V.D.M. Smit (South African Journal of Business Management, 1994)
In this article the association between accounting and market-based measures of risk on the JSE and the dependence of the association on a number of design elements are examined. The results obtained show that in the South African context a significant positive relationship exists between market beta and a variety of earnings and cash flow-based accounting betas. No evidence is found to validate the supposed superiority of cash flow-based betas over earnings-based betas. Furthermore, the results indicate that this relationship is sensitive to a number of experimental design considerations. The significance between market and accounting betas was improved when the sample size was increased, when longer time horizons were used and when the sample was restricted to companies in the same sector. The book value of equity was shown to be a better deflator than the market value.
Keywords: 650